1994
DOI: 10.1111/j.1365-2362.1994.tb01079.x
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid reduces the endotoxin‐induced lung injury in awake sheep

Abstract: Our aim was to investigate whether ascorbic acid can reduce reactive oxygen metabolite-mediated acute lung injury. The effects of intravenous administration of Escherichia coli endotoxin were studied, with and without ascorbic acid infusion, on haemodynamics, lung lymph flow, cardio-respiratory and neutrophil function in chronically instrumented sheep. Paired experiments were performed on eight sheep in which they received either endotoxin alone (0.5 micrograms kg-1 b.w.) (ET group) or in combination with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…reported that vitamin C improved sepsis and sepsisrelated organ damage [11]. In addition, a recent study showed that co-administration of vitamin C and vitamin E significantly reduced sepsis-related inflammation and organ injury in the laboratory and in the clinical state [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…reported that vitamin C improved sepsis and sepsisrelated organ damage [11]. In addition, a recent study showed that co-administration of vitamin C and vitamin E significantly reduced sepsis-related inflammation and organ injury in the laboratory and in the clinical state [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The lung injury in animal models of endotoxemia is also mitigated by vitamin C. For instance, parenteral administration of ascorbate [1000 mg/kg bolus injection followed by 200 mg/(kg.h) continuous infusion] decreases protein extravasation in the lungs of LPS-exposed sheep (15). Also, bolus injection of ascorbate or DHAA (200 mg/kg) decreases the concentration of protein in bronchoalveolar lavage fluid of LPS-exposed mice (17).…”
Section: Extravasation Of Plasma Proteins and Fluidmentioning
confidence: 99%
“…In addition, the plasma concentration of AA, which is a major antioxidant of the plasma, is often lowered. Recently, the positive effects of AA substitution on ischemia-reperfusion damage [11,12], acute respiratory distress syndrome (ARDS) [13,14], systemic inflammatory response syndrome (SIRS) and sepsis [15] were shown. These effects are ascribed to the radical scavenger activity of AA.…”
Section: Discussionmentioning
confidence: 99%